Trends in net survival from stomach cancer in six European Latin countries: results from the SUDCAN population-based study. (January 2017) - Glória, Luísa; Bossard, Nadine; Bouvier, Anne-Marie; Mayer-da-Silva, Alexandra; Faivre, Jean; Miranda, Ana
Abstract : Gastric cancers are a clinical challenge. The aim of the SUDCAN collaborative study was to compare the net survival from gastric cancer between six European Latin countries (Belgium, France, Italy, Portugal, Spain and Switzerland) and explore the trends in net survival and in the dynamics of the excess mortality rates (EMRs) up to 5 years after diagnosis. The data were extracted from the EUROCARE-5 database. First, net survival was studied over the period 2000–2004 using the Pohar-Perme estimator. For trend analyses, the study period was specific to each country. The results are reported from 1992 to 2004 in France, Italy, Spain and Switzerland and from 2000 to 2004 in Belgium and Portugal. These trend analyses were carried out using a flexible excess rate modelling strategy. There were little differences between countries in age-standardized net survival for stomach cancer (2000–2004). The 5-year net survival ranged between 26 (Spain) and 32% (Italy). There was a small increase in the age-standardized net survival at 1 year between 1992 and 2004. The increase was also observed in the 5-year net survival, except in France, where the increase was less marked. A slight decrease in the EMR between 1992 and 2004 was limited to the 24 months after diagnosis. In addition, the decrease in the EMR was the same whatever the year of diagnosis. There were minor differences in survival from stomach cancer between European Latin countries. A slight improvement in the 5-year net survival was observed in all countries and the major gain was observed during the 24 months after diagnosis. Development of innovative treatments is needed to improve the prognosis. Abstract : Supplemental Digital Content is available in the text.